Evaluating factors affecting attitudes of IT-intensive and non-IT-intensive students towards e-assessment - Bao Linh Tran; Lan Phuong Nguyen (Institute of Advanced Engineering and Science, 2023)
Despite the significant shift to distance computer-based test as an inevitable outcome of Industry 4.0 and the public lockdown of COVID-19, little effort has been made to research this new testing mode. To address this issue, this study targets two groups of information technology (IT)-intensive and non-IT-intensive students with an aim of investigating factors that effectively encourage each group to adopt online assessment and whether their majors cause any differences in the students’ attitudes. Based on the student perception of e-assessment questionnaire (SPEAQ) with some slight modifications, a final 28-item survey was formed and distributed to 400 students. Results have shown that the factors of security, and affective factors were the top factors to impact both groups of students, while the impact of validity and practicality varied among the two groups and reliability and teaching-learning were at the bottom. Besides, there were no noticeable differences in the attitudes of students coming from different majors.